Analysis of The Relationship Between Instant Noodle Consumption and Physical Activity with Adolescent Nutritional Status at MTS Al-Madani Pontianak - Virgilius Phasacola Tiko Kafaso; Yuyun Tafwidhah; Yoga Pramana (LPPM Universitas Harapan Bangsa, 2024)
Indonesia continues to experience nutritional problems across all age groups, including adolescents.. High consumption of instant noodles and the prevalence of a sedentary lifestyle can impact adolescents' nutritional status. Healthy adolescents are an investment in the nation's future; therefore, it is crucial to maintain good nutrition by regulating consumption patterns and activity levels. The aim of this study was to examine the relationship between instant noodles consumption, physical activity, and nutritional health among adolescents. This quantitative research utilized a cross-sectional approach, with 112 respondents from grades 7 and 8 at MTs Al-Madani Pontianak selected via total sampling method, meeting both exclusion and inclusion criteria. Data were collected using a food frequency questionnaire and a physical activity questionnaire. Statistical analysis employed Kendall Tau test to understand the association between instant noodles consumption, physical activity, and nutritional status. The bivariate analysis results showed a significance value of p (0.292) for the frequency of instant noodles consumption and nutritional status, and p (0.709) for physical activity and nutritional status. The study's findings indicated no significant relationship.